Direct Assembly of 2‐Oxazolidinones by Chemical Fixation of Carbon Dioxide. Issue 29 (6th June 2014) - Niemi, Teemu; Perea‐Buceta, Jesus E.; Fernández, Israel; Alakurtti, Sami; Rantala, Erika; Repo, Timo
Abstract The reaction of β‐ and γ‐haloamines with carbon dioxide to give pharmaceutically relevant 2‐oxazolidinones and 1, 3‐dioxazin‐2‐ones, was found to proceed efficiently in the presence of a base and in the absence of catalyst. After optimization of reaction conditions, the system was successfully expanded to a variety of haloamines, even at multigram scale. The reaction was further studied in silico by DFT calculations.